(untitled) (Historia, 2021)
Stating the problem: an essential point of departure in historical research? It is a general practice in academic institutions that a researcher, when undertaking a research project, clearly identifies and formulates the problem or problems which he or she wants to investigate. Among historians, however, the necessity and importance of a problem statement for doing historical research is not generally accepted. In the article both early and recent books on historical research methods are examined. It appears that many authors of handbooks on historical methodology pay little or no attention to the role of the problem statement, but that there are also a number of writers who emphasize its importance. Although the authors in the latter category all illuminate different aspects of problem statements, their viewpoints supplement rather than contradict each other. The article discusses various reasons for the negative attitude of some historians to problem statements. It is concluded that these reasons result from misconceptions about the nature of history and of historical research.